Effect of Cadmium Sulfate on high temperature Oxidation behavior of Austenitic series steel - Neelofar Amin; Mohammed Misbahul Amin; Kamarudin Hussin (2009)
Organized by Universiti Kebangsaan Malaysia (UKM), 3rd - 4th December 2008 at Danau Golf Club, Bangi, Selangor.